Association between scalp and intracerebral electroencephalographic seizure‐onset patterns: A study in different lesional pathological substrates. (11th December 2017) - Tanaka, Hideaki; Khoo, Hui Ming; Dubeau, François; Gotman, Jean
Summary: Objective: Our purpose was to determine the correlation between scalp electroencephalography (EEG) and intracerebral EEG (iEEG) seizure‐onset patterns in patients with focal lesional epilepsy to determine whether scalp seizure‐onset patterns can be specific to intracerebral seizure‐onset patterns and to lesion type. Methods: We retrospectively analyzed 61 patients with focal epilepsy and a structural magnetic resonance imaging (MRI)‐visible lesion, who first underwent extensive scalp recordings and then iEEG studies (stereo‐EEG) for presurgical evaluation, and who showed an iEEG seizure onset in the lesional/perilesional area. Five seizure‐onset patterns were recognized on scalp EEG, and 7 on iEEG, and in each patient, only the predominant scalp and iEEG seizure‐onset patterns were compared. Because scalp and iEEG recordings were acquired at different times, we followed strict criteria based on semiology and topography to match scalp with intracerebral seizures. Results: Seventy‐one pairs of seizure‐onset patterns matched between scalp and iEEG were identified. Each scalp pattern did not correspond to a single intracerebral pattern, but there were significant associations: (1) paroxysmal fast activity (≥13 Hz) at scalp onset was associated with low‐voltage fast activity at iEEG onset ( P < .001), with malformations of cortical development ( P < .001), and with superficial seizure‐onset zone based on iEEG ( P < .001); (2) rhythmic slow activity (<13 Hz) at scalp onset was associated with low‐frequency high‐amplitude periodic spikes at iEEG onset ( P = .0014), with medial temporal atrophy/sclerosis ( P < .001), and with deep seizure‐onset zone ( P < .001); and (3) repetitive epileptiform discharge at scalp onset was associated with a burst of high‐amplitude polyspikes at iEEG onset ( P = .0002). Significance: Our results disclosed that in focal epilepsy patients with seizures generated in an MRI‐visible lesion, some scalp seizure‐onset patterns are highly associated with a specific intracerebral pattern, with specific pathologies, and with the depth of seizure‐onset zone. These findings allow the interpretation of scalp seizure‐onset patterns to be significantly more informative.